RANCANG BANGUN PENDETEKSI DEHIDRASI MANUSIA BERDASARKAN WARNA URINE BERBASIS INTERNET OF THINGS (IOT) - Picara, Deya tasya; Zefi, Suzan; Rose, Martinus Mujur (Universitas Lampung, 2024)
In the current technological era, the Internet of Things (IoT) provides creative fixes for numerous health problems. The purpose of this research is to design and construct a urine color analysis system that uses the Internet of Things to identify human dehydration. Urine color is precisely measured and analyzed by the system using color and pH sensors. Data is then sent over an internet connection to a cloud-based platform.The urine color analysis results will be compared to accepted medical standards as part of the processing of the gathered data to ascertain the user's bodily hydration level. This system has a Blynk app-based user interface that offers proper hydration recommendations and real-time information about the user's level of hydration. It is anticipated that by putting this system in place, users will be able to efficiently check their level of hydration and take precautions to avoid being dehydrated. This research offers a more approachable and cost-effective method of managing one's own health in addition to aiding in the development of Internet of Things-based health technology.